Simplicity‐first model‐based plug‐in development. (25th December 2013) - Naujokat, Stefan; Neubauer, Johannes; Lamprecht, Anna‐Lena; Steffen, Bernhard; Jörges, Sven; Margaria, Tiziana; Garbervetsky, Diego; Kim, Sunghun
SUMMARY In this article, we present our experience with over a decade of strict simplicity orientation in the development and evolution of plug‐ins. The point of our approach is to enable our graphical modeling framework jABC to capture plug‐in development in a domain‐specific setting. The typically quite tedious and technical plug‐in development is shifted this way from a programming task to the modeling level, where it can be mastered also by application experts without programming expertise. We show how the classical plug‐in development profits from a systematic domain‐specific API design and how the level of abstraction achieved this way can be further enhanced by defining adequate building blocks for high‐level plug‐in modeling. As the resulting plug‐in models can be compiled and deployed automatically, our approach decomposes plug‐in development into three phases where only the realization phase requires plug‐in‐specific effort. By using our modeling framework jABC, this effort boils down to graphical, tool‐supported process modeling. Furthermore, we support the automatic completion of process sketches for executability. All this will be illustrated along the most recent plug‐in‐based evolution of the jABC framework, which witnessed quite some bootstrapping effects. Copyright © 2013 John Wiley & Sons, Ltd.